Analisa Hidrodinamika 7 (Tujuh) Bentuk Haluan Kapal (Bulbous) dengan Laju Kecepatan Konstan - Dani, Ardi Permata; Rubiono, Gatut; Mukhtar, Anas (Virtual of Mechanical Engineering Article, 2019)
Technology developments in the maritime sector, especially shipping has experienced a significant increase. One of them is the technological development of ship parts such as a bow. The aim’ of this development is to determine the shape of the ship's bow that is most effective when moving. The study was conducted using miniatures resembling 7 bulbous forms. Dimensions of the pool are 150 x 30 x 8 cm, type of fluid used is seawater without currents. Ship's propulsion uses 6-volt dynamo. Travel time is measured using a stopwatch by taking data 3 times in each form of a bow. Data analysis is based on the average inhibitory coefficient (Cd) value that occurs. The results of the study show the shape of the bowel influences rate of speed and drag coefficient of the ship. The oblique direction I produce a drag coefficient (Cd) of 0.27 when the ship moves, so speed and travel time are more maximal than the other 6 bow directions.